2007
DOI: 10.5897/ajb2007.000-2383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of ethanolic extract of Croton zambesicus on the testes of Swiss albino mice

Abstract: The possible effect of Croton zambesicus administration on vital organs has been less investigated despite its extensive traditional use in tropical Africa. We therefore aim at elucidating the effect of ethanolic extract on the testes. The aqueous fraction of ethanolic leaf extract of C. zambesicus (5 and 10 mg/Kg body weight) was administered to verify its effect on sperm concentration, sperm motility, sperm progessivity, malondialdehyde and catalase activities for a period of five consecutive days. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…These two types differ morphologically and biochemically [8][9][10][11] . Accidental cell death is regarded as necrotic and could result from extrinsic insults to the cell such as osmotic, thermal, toxic and traumatic effects [11][12][13] . Pathological cell death is regarded as apoptotic and is an organized programmed cell death (PCD) that is mediated by active and intrinsic mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two types differ morphologically and biochemically [8][9][10][11] . Accidental cell death is regarded as necrotic and could result from extrinsic insults to the cell such as osmotic, thermal, toxic and traumatic effects [11][12][13] . Pathological cell death is regarded as apoptotic and is an organized programmed cell death (PCD) that is mediated by active and intrinsic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…G. kola seeds contain biflavonoid possessing antiinflammatory properties [4] and are a natural antioxidant [1][2][3][4] . Constituents of the seed of G. kola include [1][2][3][8][9][10][11] benzophenones, Garcinia biflavonones (GB-1, GB-2) and kola flavonone [2,3] . Apigenin based flavonoids represent 60% of the total flavonoids present in the diethyl ether fraction of G. kola seed [4] .…”
Section: Introductionmentioning
confidence: 99%
“…From the above paragraphs, many beneficial effects of medicinal plants on male reproductive function are associated with antioxidant effects [35,37,56,61,73]. This suggests that the potential of phytomedicines to improve male fertility is due to presence of antioxidants.…”
Section: Discussionmentioning
confidence: 92%
“…Administration of the ethanol extract of Croton zambesicus at the dose of 5 and 10 mg/kg in vivo increased the sperm number and motility, but decreased malonic aldehyde levels and catalase activity in healthy mice after five days of treatment [56]. Korean ginseng (P. ginseng) administered at the dose of 1 g/kg for 56 days in male rats increased sperm count and motility, testis cAMP-responsive element modulator (CREM) mRNA and CREM protein [57].…”
Section: Medicinal Plants and Sperm Abnormalitiesmentioning
confidence: 99%
“…Also, ethanolic extract of sesame enhances morphology of the spermatozoa in the epididymis at the time of sacrifice of the animals (Saalu et al, 2007b Ofusori et al (2007) evaluated the effect of ethanolic extract of croton zambesicus (as a potent antioxidant and free radical scavenger) on the testes of swiss albino mice and reported that there was a significant increase in the sperm concentration, motility, and progressivity in the treated group rather than the control group. This significant increase was observed to be dose dependent C. zambesicus.…”
Section: Serum Hormone (Lh Fsh and T) Levelsmentioning
confidence: 99%